The Use of The STEPWISE Method The Effect of Cultivated Area On Agricultural Production in Iraq - Abbas Fadhil Kreah; Ali Ghani Nori (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
One of the important problems addressed by researchers and specialists is the problem of agriculture and agricultural land and how to sustain or address them in the event that they need a certain treatment or work is being done to develop methods and agricultural tools and patterns used, which in turn affects production, and in this research has been working to study the impact of several factors on production and has been selected specific workers agricultural land, which is harvested land and affected land and total land and has Mathematical statistical methods were used in the analysis and the STIPWISE method of linear regression was used to determine the effect and any variables affecting and not affecting the dependent variable, which is agricultural production, and the results of the paper found that one of the variables does not affect the dependent variable, which is the harvested land variable.